(untitled) (Journal of actual problems of jurisprudence, 2016)
In this article is examined guilt and the form of guilt, also the concept of the degree of guilt in the criminal law of the Republic of Kazakhstan. The degree of guilt – is a quantitative characteristic of the social essence of guilt, which is determined by a combination of form and content of fault with all the features of the mental attitude of a person to the objective circumstances of the crime and its subjective, psychological reasons. The author makes the analysis of the historical development of the institution of guilt, a form of guilt in the foreign criminal law and the role of guilt in qualifying of criminal cases.